Partial repair in irreparable rotator cuff tear: our experience in long-term follow-up - Di Benedetto, E. D.; Di Benedetto, Paolo; Fiocchi, Andrea; Beltrame, Alessandro; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2017)
Aim of the work: Massive rotator cuff tears are a common source of shoulder pain and dysfunction, especially in middle age patient; these lesions represent about 20% of all rotator cuff tears and 80% of recurrent tears. Some lesions are not repairable or should not be repaired: in this case, a rotator cuff partial repair should be recommended. The aim of the study is to evaluate the outcome of rotator cuff partial repair in irreparable rotator cuff massive tear at medium and long-term follow-up. Materials and method: We have evaluated 74 consecutive patients treated with functional repair of rotator cuff by the same surgeon between 2006 and 2014. We divided patients into 2 groups, obtaining 2 average follow-up: at about 6,5 (group A) and 3 years (group B). In December 2015, we evaluated in every patient ROM and Constant Score. We analyzed difference between pre-operatory data and the 2 groups.  Results: We found statistical significant difference in ROM and in Constant Score between pre-operatory data and group A and group B. Between group A and group B there is relevant difference in Constant Score but not in ROM. Conclusions: Partial repair can give good results in a medium follow-up, in terms of pain relief and improvement of ROM, as well as in quality of life. Difference in ROM and Constant Score between group A and group B may indicate the begin of partial repair failure; according to our data, 6-7 years may be the time limit for this surgery technique.